Yes, We Are!: An Examination of Teachers' Understanding of their Work as Part of a Profession - Wall, Chantal (University of Waterloo, 2011)
The sociological literature on professions often portrays medicine and law as ideal-type professions. This is asserted largely on the basis of a list of criteria that tends to commonly include: extended education, specialized knowledge, prestige and autonomy. Other occupations, such as teaching, are seen to not measure up. This study questions the legitimacy of this claim and the relevance of literature, which does not seem to recognize the current reality of teacher’s work. Based on data collected through interviews with high school teachers, it becomes clear that they see themselves in a very different light. The issues that are of particular interest are the way the education system’s structure actually increases teacher autonomy and the importance of self-perception to professionalism. The need to reassess the literature is argued in light of these missing elements.
Keywords: teaching; professions; Sociology